2013
DOI: 10.3892/br.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to bisphenol A during pregnancy and lactation on the testicular morphology and caspase-3 protein expression of ICR pups

Abstract: Abstract. Bisphenol A (BPA), a xenoestrogen and endocrine-disrupting chemical, is a cause for concern due to its being a potential human carcinogen. The aim of this study was to investigate the effects of continued maternal exposure to BPA on the testicular structures and expression of caspase-3 protein in male ICR offspring during pregnancy and lactation and explore its possible mechanism. Pregnant ICR mice were divided into two control groups, which were either given or not given the solvent dimethyl sulfoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…However, the BPA-treated group showed a statistically significant increase in the number of caspase-3-positive cells in comparison with that of the control. Similarly, increased apoptosis with elevated expression of caspase-3 was detected in the testes of mice pups exposed to BPA during pregnancy and lactation (Liu et al 2013). Moreover, similar findings were observed in the liver of rats treated with BPA (Xia et al 2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the BPA-treated group showed a statistically significant increase in the number of caspase-3-positive cells in comparison with that of the control. Similarly, increased apoptosis with elevated expression of caspase-3 was detected in the testes of mice pups exposed to BPA during pregnancy and lactation (Liu et al 2013). Moreover, similar findings were observed in the liver of rats treated with BPA (Xia et al 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, increased apoptosis with elevated expression of caspase‐3 was detected in the testes of mice pups exposed to BPA during pregnancy and lactation (Liu et al . ). Moreover, similar findings were observed in the liver of rats treated with BPA (Xia et al .…”
Section: Discussionmentioning
confidence: 97%
“…Peritubular myoid cells maintain the morphology of the seminiferous tubules participating in the formation of the basement membrane. It was showed, that exposure in prenatal life to BPA resulted in apoptosis of pertitubular myoid cells in testis of 21 days old mice [70]. The same effect was observed in adult rats treated with cimetidine which has weak antiandrogenic properties [71].…”
Section: Discussionsupporting
confidence: 50%
“…A number of studies point out that the adult exposure BPA can reduce sperm production and efficiency of spermatogenesis [33,34] . Liu et al found that exposure of pregnant mice to BPA during pregnancy and lactation has some toxic effects on the testes of male offspring and these may originate from increased apoptosis [35] .…”
Section: Discussionmentioning
confidence: 99%